Association between pan-immune-inflammation value and clinical outcomes in critically ill patients with hyperlipidemia: An observational study - Xiao-Ying Huang; Xiang Zheng (PLoS ONE, 2026)
Background Hyperlipidemia contributes to immune-inflammatory imbalance and poor outcomes in critical illness. The pan-immune-inflammation value (PIV), derived from neutrophil, monocyte, platelet, and lymphocyte counts, may capture this burden, but its prognostic value in critically ill patients with hyperlipidemia is unclear. Methods We conducted a retrospective cohort study using MIMIC-IV (v3.1). Adults with a first ICU admission and ICD-coded hyperlipidemia, with complete blood counts within 24 h, were included. lnPIV (ln-transformed PIV) was analyzed as continuous and categorical (quartiles) exposures. Primary outcomes were 28-, 90-, and 180-day mortality; secondary outcomes included ICU and in-hospital mortality, acute kidney injury (AKI), and delirium. Survival, Cox regression, restricted cubic spline (RCS), and ROC analyses were applied. Results Among 12,408 patients (mean age 70 years; 38.6% female), 1,309 died in hospital. Higher lnPIV was independently associated with 28-day (HR = 1.14, 95% CI: 1.10–1.18), 90-day (HR = 1.15, 95% CI: 1.11–1.18), and 180-day mortality (HR = 1.13, 95% CI: 1.10–1.16; all P < 0.001). RCS analysis identified a threshold at PIV ≈ 172, above which mortality risk increased sharply. The highest quartile had significantly greater in-hospital mortality risk (OR = 1.85, 95% CI: 1.50–2.29). Adding PIV to the SOFA score significantly improved discrimination (AUC increased from 0.55 to 0.67, P < 0.001) and provided positive net benefit across clinically relevant threshold probabilities. lnPIV was also associated with AKI and delirium. Conclusion Elevated PIV is independently associated with mortality and adverse outcomes in critically ill patients with hyperlipidemia. As a simple and readily available composite marker, PIV may complement existing risk scores for early risk stratification in this vulnerable population.